Lebih dari Sepiring Gizi: Kajian Literatur Peran Gizi terhadap Children Well-Being Anak Usia Dini - Ai Nurjanah; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study examines the holistic role of nutrition beyond physical growth by focusing on its contribution to the overall well-being of early childhood. While nutrition is commonly associated with physical health, this literature review highlights its influence on cognitive, emotional, and social development, which collectively represent children's well-being. Using a qualitative literature review approach, this study synthesizes findings from various academic sources to analyze how the adequacy of macro- and micronutrients supports psychological stability and learning readiness. The findings show that proper nutrition is associated with reduced anxiety, improved concentration, and better social adaptability in children. In addition, the concept of